1988
DOI: 10.1002/ijc.2910410307
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐associated alpha‐2‐macroglobulin in human melanomas

Abstract: We and others have previously shown that human melanoma cell lines in culture synthesize alpha-2-macroglobulin (alpha 2M). We have now studied melanomas from 30 patients for the presence of alpha 2M using the peroxidase anti-peroxidase technique on histologic sections from paraffin-embedded tissues and primary antibody raised against tumor-associated alpha 2M in rabbits. alpha 2M was detected in 10 of the 30 melanomas studied. In all but 2 cases the presence of alpha 2M was restricted to solitary tumor cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
2

Year Published

1990
1990
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 12 publications
0
9
0
2
Order By: Relevance
“…Moreover, immunohistochemical studies have suggested a poor prognosis for patients with a,-AT-, a,-MG-and PSTI-rich tumors (Tahara et al, 1984;Matoska et al, 1988;Higashiyama et ab, 1990). Immunohistochemically, the incidence of a,-AT is markedly higher in advanced colorec-LC-l/sq.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, immunohistochemical studies have suggested a poor prognosis for patients with a,-AT-, a,-MG-and PSTI-rich tumors (Tahara et al, 1984;Matoska et al, 1988;Higashiyama et ab, 1990). Immunohistochemically, the incidence of a,-AT is markedly higher in advanced colorec-LC-l/sq.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this protective role of α 2 -macroglobulin may further justify the shift of zinc towards this metalloprotein in cervical carcinoma. On the other hand, increases in α 2 -macroglobulin have been also found in tumour experimental models (Mackiewicz et al, 1993) and in melanoma patients, although such increments were associated with unfavourable prognosis (Matoska et al, 1988). This is not surprising because the shift of zinc results in a low zinc bioavailability with consequent reduction in peripheral thymulin molecules saturated by zinc ions, resulting in reduced zinc-bound active thymulin and impairment of immune efficiency against tumours.…”
Section: Discussionmentioning
confidence: 93%
“…In this context, α 2 -macroglobulin may play a key role for two reasons: firstly, because of a high K d for zinc (10 -10 M) (Giroux, 1975) and, secondly, because α 2 -macroglobulin is implicated as an inhibitor of matrix metalloproteases (MMPs) (Enghild et al, 1989) against invasive tumour proliferation ( Stetler-Stevenson et al, 1993). Indeed, increases in α 2 -macroglobulin have been reported in experimental neoplasia (Mackiewicz et al, 1993) and in melanoma patients (Matoska et al, 1988). Therefore, we measured plasma levels of zinc, of active thymulin (Zn-FTS) and of α 2 -macroglobulin in patients affected by locally advanced cervical carcinoma.…”
mentioning
confidence: 99%
“…In this connection, a bad prognosis has been suggested for patients with ~2M containing tumors (Tahara et al 1984;Matoska et al 1988;Kataoka et al 1989).…”
Section: Discussionmentioning
confidence: 98%